GAMBARAN TINGKAT KEMANDIRIAN LANSIA DALAM PEMENUHAN ACTIVITY DAILY LIVING DI ROUJIN HOME SEIFUEN SHIKINA, OKINAWA JEPANG - Husnul Nur Afiah; Murniati; Siti Haniyah (Bajang Institute, 2023)
Japan is faced with problems related to population growth. As a result As a result, the population structure in Japan shows the condition of an aging society with another name Koreika Shakai This study is intended to understand the description of the level of independence in fulfilling daily activities in the elderly at Roujin Home Shikina Saefuen, Okinawa Japan. The method used in this research is descriptive quantitative. The instrument used in this study was the Barthel index (validity value r > 0.4438 and reliability value 0.884). The results showed that the elderly were more than 90 years old, the elderly were female, and most of them were mildly dependent. It can be concluded that the elderly at Roujin Home Seifuen Shikina are very old, dominated by women, most of whom need partial assistance in fulfilling Activity Daily Living (ADL).